Phonomyography as a non-invasive continuous monitoring technique for muscle ischemia in an experimental model of acute compartment syndrome. Issue 11 (November 2017) - Martinez, Adriana P.; Moser, Thomas P.; Saran, Neil; Paquet, Marilène; Hemmerling, Thomas; Berry, Greg K.
Abstract: Background: In acute compartment syndrome (ACS), clinicians have difficulty diagnosing muscle ischemia provoked by increased intra-compartmental pressure in a timely and non-invasive manner. Phonomyography records the acoustic signal produced by muscle contraction. We hypothesize that alterations in muscle contraction caused by muscle ischemia can be detected with phonomyography, serving as a potential non-invasive technique in the detection of ACS. Methods: The left hind limb of 15 Sprague-Dawley rats was submitted to a reversible ischemic model of limb injury for 30 min and 1, 2, 4, 6 h (3 rats in each group). The right limb served as control. Phonomyography microphones were placed over the posterior calf of both limbs and the sciatic nerve was stimulated percutaneously at 10-min intervals to evaluate muscle contraction. Histopathological analysis of muscles and nerves biopsies was performed and correlation was made between duration of injury, phonomyography output and degree of muscle and nerve necrosis. Results: There was a statistically significant decrease in the phonomyography signal output in the ischemic limb that correlated with the duration of ischemia and histological findings of muscle and nerve necrosis. The phonomyography signal decrease and histological findings were respectively: 55.5% (n = 15;p = 0.005) with rare muscle and nerve necrosis at 30 min, 65.6% (n = 12;p = 0.005) with 5–10% muscle necrosis at 1 h, 68.4% (n = 9;p = 0.015) with 100% muscle necrosis and little nerve damage at 2 h, 72.4% (n = 6;p = 0.028) with 100% muscle necrosis and severe nerve damage at 4 h, and 92.8% (n = 3;p = 0.109) with 100% muscle necrosis and severe nerve degeneration at 6 h. Conclusion: Changes in phonomyography signal are observed in early ischemic injury prior to the onset of nerve or muscle necrosis. Therefore, phonomyography could serve as a non-invasive technique to detect early ischemic muscle changes in acute compartment syndrome. Clinical relevance: The detection of abnormal muscle contraction in a timely fashion and non-invasive manner is of interest in clinical settings where the presence of ischemia is not easy to diagnose.